The role of supervisory controls in reducing the operational risks associated with electronic systems in the National Bank of Iraq (Entrepreneurship Journal for Finance and Business, 2025)
The research seeks to determine and measure the effectiveness of the supervisory controls adopted in the National Bank of Iraq in reducing the operational events related to electronic systems in terms of the number of events and the size of the losses resulting from them, through the use of the inductive approach in terms of examining data on operational events and supervisory controls in the years 2020 and 2021 and applying theoretical concepts. Which were discussed to evaluate the effectiveness of internal controls in reducing operational risks. As a result, the study reached a number of conclusions, the most important of which is that internal controls contribute to reducing the number and size of operational events related to electronic systems and maintaining them within acceptable risk limits